The effects of albumin concentration to outcome of acute respiratory distress syndrome (ARDS) patients in intensive care unit RSUP Dr. Sardjito Yogyakarta - Novia Etty Parmawati (Acta Interna The Journal of Internal Medicine, 2013)
ABSTRACTBackground: Hipoproteinemia mostly happened in critically ill patients, including ARDS, and usually comes toworst clinical appearance. Early ARDS is characterized by a rising of the permeability in the alveolar-capillarybarrier, leading to an infl ux of fl uid into the alveoli, and albumin also has a major role to control the osmolatoryof plasma.Aim: The aim of the study was to know about the effect of the albumin concentration to outcome (survivor/nonsurvivor) of the ARDS patient in the Intensive Care Unit (ICU) RSUP Dr. Sardjito.Methods: This study used cross-sectional method. The samples of this study were the patients at the ICU RSUPDr. Sardjito Yogyakarta, from January 2009 until December 2011. The diagnosed of ARDS based on EACCcriteria. The inclusion criteria were people with age ≥ 18 years old, fulfi ll diagnostic criteria of ARDS, and treatedin ICU. The demography, laboratory result, and curing process, have been tested statistically in SPSS 17. Thevariable was analyzed by chi-square and Mann-Whitney test, signifi cantly considered if p < 0,05.Results: The samples who fulfi ll these criteria were 61 patients. Mostly women (54,1%) with 49 years-old rangeand the result were 34 patients (55,7%) died. The biggest cause of ARDS was pneumonia (60,7 %) and thebiggest Comorbid was malignant (21,6%). The mortality rate of ARDS was 5,75%. The result of univariat analysiswas the increased of transaminase enzyme (p 0,007), COPD Co morbid (p 0, 02) and length of stay in the ICU (p= 0,021) which was signifi cantly given effect to the outcome of the patients. The survivors have higher albuminconcentration (2, 6) than in non survivors (2, 4), although not statistically signifi cant (p = 0,621).Conclusion:The albumin concentration did not have a statistically signifi cant effect to the outcome of the ARDSpatient in ICU RSUP Dr. Sardjito Yogyakarta. The main factor was the increase of transaminase enzyme, Comorbid COPD, and length of stay in the ICU.Keywords: ARDS, albumin concentration, ICU